Evidence for mineral stratification in a zoned basaltic magma body at Kīlauea Volcano, Hawai’i: insights from the Kulanaokuaiki-3 tephra (≥ 1.0 ka) - Lynton, Stephen J.; Rose, Timothy R. (Contributions to mineralogy and petrology, 2025)
Mineral stratification has long been inferred to develop in basaltic magma bodies within the summit of Kīlauea Volcano, HI, primarily as a result of gravitational settling or redistribution of early crystallizing olivine, as indicated, particularly, in studies of Hawaiian lava lakes. Direct evidence from Kīlauea’s voluminous lava flows of such mineral stratification has been lacking or subject to challenge, however, because of magma mixing, post-eruptive reequilibration, and evidence that flows initially thought to derive from a single magma body had multiple sources. Tephra from Kīlauea’s Kulanaokuaiki-3 eruption ( ≥ 1.0 ka) offers an unusual manifestation of vertical stratification among phenocryst phases. The tephra deposits appear to constitute inverted products of a magma body comprising a lower zone enriched in olivine phenocrysts and an olivine-depleted upper zone enriched in plagioclase and clinopyroxene phenocrysts. Small proportions of microphenocrysts of all three phases occur throughout both zones. A relatively narrow compositional range among most olivine—Fo 80–82 in the lower zone and Fo 78–80 in the upper zone—suggests reequilibration within that magma body during cooling. Combined with a range in plagioclase compositions—generally, An 69–73 in the lower zone and An 63–68 in the upper—and other data, the analyses also suggest a slight change in conditions, such as a narrow thermal gradient, between the lower and upper zones of that magma body. A comparison with studies of Kīlauea’s lava lakes suggests broad similarities in stratification among olivine, plagioclase, and clinopyroxene phenocrysts. One feature commonly found in lava lakes—segregation veins—also is suggested by pumice and differentiated lithic blocks, whereas other features, such as pipelike olivine-rich bodies, have not been documented in the Kulanaokuaiki-3 deposits. The stratified body inferred from these deposits offers a model for zonation applicable to similar shallow, basaltic magma bodies.